Gifts: intertwining market and moral economies and the rise of store bought gifts. Issue 3 (4th May 2017) - Weinberger, Michelle F.
ABSTRACT: Gifts are a major part of both economic and social life. This intertwined relationship between the market and moral economies has long been unsettling to those concerned about rationalized marketplace meanings contaminating and eroding the sacred social role of gift giving. Consumer researchers have analysed the important relationship work done through gift giving in the moral economy and the ways that the marketplace facilitates such work (or not). However, little has explored when, how, and why a store bought gift, rather than a homemade one, actually became acceptable. This article uses three case studies from the early to mid-1800s to trace the rise of the store bought gift in the American marketplace. It highlights how the sociocultural context, marketing innovations, retailers, and meanings surrounding gifting all helped to ensconce gift giving as both a central component in the contemporary marketplace and a tool for symbolic communication in social life.